The Constructivist Regard for Science. On Richard Rorty and Bruno Latour (Diametros, 2019)
The aim of the article is to answer how one can be a constructivist and treat science as one of the greatest achievements of contemporary societies at the same time. Since constructivism is a broad trend with many variations, the author focuses only on two of its members: Richard Rorty and Bruno Latour. He tries to show that, ,one can give a coherent answer to the question by combining selected aspects of their views. Although both Rorty and Latour reject a realistic account of science, they claim that science is an effective way of dealing with the world or, to use Latour’s term, with nonhumans. It is the pragmatic category of “dealing with reality”, rather than the philosophical ideas of representation or correspondence, that explains the high status of science. Both thinkers emphasize that the effective interactions with nonhumans are a consequence of the specific culture of cooperation and supervision which is typical of science.
Keywords: constructivism; science; Richard Rorty; Bruno Latour; Actor-Network Theory; neopragmatism